2007
DOI: 10.1523/jneurosci.4497-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in Collapsin Response Mediator Protein-1 Exhibit Impaired Long-Term Potentiation and Impaired Spatial Learning and Memory

Abstract: Collapsing response mediator protein-1 (CRMP-1) was initially identified in brain and has been implicated in plexin-dependent neuronal function. The high amino acid sequence identity among the five CRMPs has hindered determination of the functions of each individual CRMP. We generated viable and fertile CRMP-1 knock-out (CRMP-1 Ϫ / Ϫ ) mice with no evidence of gross abnormality in the major organs. CRMP-1 Ϫ / Ϫ mice exhibited intense microtubule-associated protein 2 (MAP2) staining in the proximal portion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 56 publications
3
74
0
2
Order By: Relevance
“…As the mean spine area of crmp1 Ϫ/Ϫ layer V neurons stained by the Golgi-impregnation method was smaller than that of crmp1 ϩ/Ϫ (see Results), CRMP1 may play a role in establishing stable synapses. This idea of CRMP1 as a regulator of synaptic transmission is consistent with a recent observation that crmp1 Ϫ/Ϫ mice show impaired long-term potentiation, learning, and memory (Su et al, 2007). Several lines of evidence suggest that Cdk5 plays an essential role in modulating synaptic transmission (Cheung et al, 2006).…”
Section: I-positive Clusters Was Markedly Attenuated In Crmp1supporting
confidence: 87%
“…As the mean spine area of crmp1 Ϫ/Ϫ layer V neurons stained by the Golgi-impregnation method was smaller than that of crmp1 ϩ/Ϫ (see Results), CRMP1 may play a role in establishing stable synapses. This idea of CRMP1 as a regulator of synaptic transmission is consistent with a recent observation that crmp1 Ϫ/Ϫ mice show impaired long-term potentiation, learning, and memory (Su et al, 2007). Several lines of evidence suggest that Cdk5 plays an essential role in modulating synaptic transmission (Cheung et al, 2006).…”
Section: I-positive Clusters Was Markedly Attenuated In Crmp1supporting
confidence: 87%
“…This supports previous observations that CRMP1 is predominantly expressed in neurons (Bretin et al 2005), suggesting that abnormal dysregulation of the protein in HD brains might contribute to the neurodegenerative disease phenotype. A potential importance of CRMP1 for neuronal function under physiological conditions is also supported by gene knockdown studies in mice, indicating that CRMP1 function is critical for learning and memory (Su et al 2007). Thus, for further more detailed experimental investigations, we focused our efforts on the protein CRMP1, which likely is a neuron-specific modulator of mutant HTT misfolding and aggregation in brains of HD patients.…”
Section: Interaction Network Filtering Enables the Identification Of mentioning
confidence: 89%
“…CRMP1 is a cytoplasmic phosphoprotein that is predominantly expressed in neurons (Goshima et al 1995). Previous studies revealed that mice lacking CRMP1 show impairment of learning and memory (Su et al 2007), suggesting that a reduction of CRMP1 levels in HD brains might contribute to the disease phenotype (Paulsen et al 2013). This view is also supported by studies in cell model systems, indicating that reduced levels of CRMP1 promote death of spinal cord neurons (Kurnellas et al 2010).…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…Previous studies have reported that cytoskeletal regulation is also involved in synaptogenesis. For example, activation of GSK-3␤ and loss of CRMP-1 inhibits LTP with synapseassociated impairments (Zhou and Snider, 2005;Su et al, 2007, Yamashita et al, 2007. In addition, Rac1 regulates dendritic spine density and shape in rat and mouse pyramidal neurons (Nakayama et al, 2000;Tashiro and Yuste, 2004).…”
Section: Discussionmentioning
confidence: 99%